(untitled) (The Research of Medical Science Review, 2025)
Background: Patient education is a vital role in the provision of healthcare, and nurses perform critical role in facilitating effective patient learning. The results of this study provide a comprehensive view of the knowledge, attitude, and practice of patient education among nurses at tertiary care hospitals of Peshawar, shedding light on various aspects that influence the delivery of healthcare services. Objective: To investigate the knowledge, attitude, and practice of patient education among nurses. Methodology: The current cross-sectional study included 197 registered nurses from lady reading, Hayatabad medical complex and Khyber teaching hospital of Peshawar Pakistan. The data was gathered using a self-administered questionnaire, and SPSS was utilized for analysis. The study participants were chosen by a convenient sampling technique. Results: The demographic analysis revealed a predominance of female nurses (84.1%), with the majority aged 26-30 years (51.7%). Educational qualifications varied, with 55.4% holding diplomas and 44.6% possessing BSN degrees. Marital status showed a near-equal split between single (46.3%) and married nurses (53.7%). Knowledge scores averaged at 16.31 out of 20, indicating a moderate understanding of patient education principles, with female nurses scoring slightly lower than males. Practice scores averaged at 15.65, reflecting varied implementation of patient education strategies, and attitude scores averaged at 15.77, denoting generally positive perceptions towards patient education. Significant correlations were found between knowledge and attitude (r = 0.367) and attitude and practice (r = 0.412), suggesting that higher knowledge levels are associated with more positive attitudes and better educational practices. Conclusion: In conclusion, the demographic insights and analysis of knowledge, attitudes, and practices regarding patient education among nurses highlight opportunities for improving nursing practices and patient outcomes. By addressing identified needs and leveraging current strengths.